2020
DOI: 10.1209/0295-5075/129/28002
|View full text |Cite
|
Sign up to set email alerts
|

Model for clustering of living species

Abstract: Clusters appear in nature in a diversity of contexts, involving distances as long as the cosmological ones, and down to atoms and molecules and the very small nuclear size. They also appear in several other scenarios, in particular in biological systems as in ants, bees, birds, fishes, gnus and rats, for instance. Here we describe a model composed of a set of female and male individuals that obeys simple rules that rapidly transform an uniform initial state into a single cluster that evolves in time as a stabl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Importantly, the new individual is settled only if the total number of individuals in the neighborhood (within a distance R = 0.1) does not exceed a threshold value M . This local constraint of maximum number of individuals is a significant difference from our previous model where only a global constraint for the maximum number of total population was assumed [14]. Another important change comparing to our previous model is mov and rep could be different.…”
Section: The Modelmentioning
confidence: 78%
See 1 more Smart Citation

Mobility driven coexistence of living organisms

de Oliveira,
de Moraes,
Bazeia
et al. 2021
Preprint
Self Cite
“…Importantly, the new individual is settled only if the total number of individuals in the neighborhood (within a distance R = 0.1) does not exceed a threshold value M . This local constraint of maximum number of individuals is a significant difference from our previous model where only a global constraint for the maximum number of total population was assumed [14]. Another important change comparing to our previous model is mov and rep could be different.…”
Section: The Modelmentioning
confidence: 78%
“…In a previous paper we studied a simple model of clustering in which female and male individuals followed a basic rule of reproduction, die and movement and demonstrated that a uniformly distributed population can transform into a state where species form a huge single cluster [14]. While the centre of this aggregation moves randomly its size follows a power law behavior in terms of the number of individuals in the whole population.…”
Section: Introductionmentioning
confidence: 99%

Mobility driven coexistence of living organisms

de Oliveira,
de Moraes,
Bazeia
et al. 2021
Preprint
Self Cite
“…But there are cases where off-lattice simulations seem to be more appropriate, hence we can not avoid the numerical difficulties of the latter models. We just quote here some microbiological systems, but other situations, like collective movement or floating may also require off-lattice modeling [52,53,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the latter technique is more demanding and requires larger numerical efforts, but in certain cases we cannot avoid this difficulty. For example this is the proper way to study certain phenomena, like clustering 61 , 64 .…”
Section: Introductionmentioning
confidence: 99%